An insight into ignition factors and mechanisms of magnesium based materials: A review. (5th January 2017) - Tekumalla, Sravya; Gupta, Manoj
Abstract: There has been a spurt in the quest for ignition resistant Mg materials that can be employed in the aerospace sector, consequent to the recent lifting of the ban on magnesium based materials by Federal Aviation Administration (FAA). Literature studies show some advances in the field of development of ignition proof Mg materials. This article aims at capturing the currently available data on the ignition properties of Mg based materials. One of the objectives of this article is to reduce the ambiguity between ignitability and flammability of Mg materials and bridge the gap in understanding by clearly demarcating the tests and standards available for the two. Further, most importantly, the factors affecting the ignition temperatures of Mg materials and their mechanisms are emphasized such that an informed approach can be undertaken while designing the Mg based alloys for the aerospace applications. This article also demonstrates and emphasizes that the studies on the ignitability can be stretched to new classes of materials like LPSO (Long Period Stacking Order) alloys and nanocomposites in order to attain a maximized benefit in the existing domain of materials of Mg base. Graphical abstract: Highlights: A review of the current advances in the field of ignition resistant Mg materials Differentiation between ignitability and flammability of Mg materials Focus on the factors and mechanisms affecting the ignition temperature Geometrical factors, testing conditions and metallurgical factors with supporting mechanisms Evidence for the need to establish further mechanisms on ignitability of new class of Mg materials